Malondialdehyde Serum Levels in Patients with Systemic Sclerosis Relate to Dyslipidemia and Low Ventricular Ejection Fraction - Zeina Ibrahim-Achi; Pablo Jorge-Pérez; Pedro Abreu-González; Raquel López-Mejías; Candelaria Martín-González; Miguel Á. González-Gay; Iván Ferraz-Amaro (MDPI AG, 2023)
Systemic sclerosis (SSc) is a chronic disease characterized by vasculopathy with the involvement of dysfunctional microcirculatory vessels. Features of the disease include progressive fibrosis of the skin and internal organs and systemic inflammation characterized by the presence of circulating autoantibodies and proinflammatory cytokines. Furthermore, macrovascular disease and atherosclerosis are more common in patients with SSc than in the general population. Oxidative stress plays a crucial role in the development of several processes, including endothelial dysfunction, cancer, inflammation, and atherogenesis. Malondialdehyde (MDA) is a well-established marker of oxidative stress. In this work, we have analyzed the relationship between serum MDA levels and clinical, laboratory, and vascular characteristics in a well-characterized cohort of 53 patients with SSc. A multivariable analysis was performed to study the relationship between circulating MDA and disease characteristics in patients with SSc. Cardiovascular assessment was also performed, including ultrasonography of the carotid and aorta, and echocardiography. MDA showed a significant and positive relationship with the serum levels of lipid profile molecules such as total cholesterol (β coefficient = 0.006 (95% CI: 0.0004 to 0.01), nmol/mL, p = 0.037) and LDL cholesterol (β coefficient = 0.008 (95% CI: 0.001 to 0.01) nmol/mL, p = 0.017). On the contrary, most manifestations of the disease, including skin, lung, and joint involvement, as well as the presence of digital ulcers, were not related to MDA. However, high MDA levels were significantly and independently associated with lower ventricular ejection fraction after adjustment for covariates (β coefficient = −0.04 (95% CI: −0.06 to −0.02), nmol/mL, p = 0.001). In conclusion, serum MDA levels were related to higher levels of total and LDL cholesterol and a lower left ventricular ejection fraction in patients with SSc. MDA could serve as a potential biomarker of dyslipidemia and heart failure in SSc.